John Howard’s High Park: “A Square Mile or Two of Rough Ground…” - Bain, David (Ontario History)

(untitled) (The Ontario Historical Society, 2009)
In 1837, architect John George Howard purchased 165 acres west of Toronto as a country estate that he named High Park. In 1876, he donated his land to the city and, almost until his death in 1890, was the primary force behind the planning and development of a natural or forest park that is almost 400 acres in size today. This article looks at John Howard’s efforts during his lifetime, as well as his continuing influence in the decades after his death. It also examines the idea of a forest park in an urban setting, and the ideas, events and individuals that have shaped one of Canada’s important urban parks.